Are we underestimating the real burden of malnutrition? An experience from community-based study - Disha Agarwal; Sunil Kumar Misra; Shailendra Singh Chaudhary; Gyan Prakash (Wolters Kluwer Medknow Publications, 2015)
Background: Since the inception of childhood nutritional programs in India, underweight has been taken to judge the nutritional status of children; but is it a true indicator of overall prevalence of malnutrition in a community? Objective: To estimate the overall prevalence of malnutrition by using Composite Index of Anthropometric Failure (CIAF) and to assess its usefulness over various conventional anthropometric indicators among under 5 children residing in Agra city. Materials and Methods: A cross-sectional, community-based study was conducted among under 5 years age children, from June 2012 to July 2013 in an urban slum of Agra. Nutritional status was assessed using anthropometry and clinical examination, and classified as per World Health Organization (WHO) 2006 Growth Standards and CIAF. Results: Of the 458 children studied, 42.8% were underweight, 41.9% had stunting, while 22.7% had wasting. However, 60.04% of children were found to be malnourished as per the CIAF. Unlike three conventional anthropometric indicators of malnutrition, CIAF was observed to have a much consistent association with morbidity like diarrhea episodes in past 3 months (odds ratio (OR) = 2.09), acute respiratory tract infection (ARI) episode in past 3 months (OR = 1.58), and any illness requiring hospitalization (OR = 1.29). Conclusion: The CIAF should supplement the conventional indices of malnourishment, to provide a single, aggregated figure of actual number of undernourished children in a given population.